The densities of fiber follicles in the Karakaş, Norduz, and Zom sheep and a comparative analysis - Tuncer, Selçuk S.; Uslu, Sema; Taş, Abuzer; Şireli, Halit D. (Austral Journal of Veterinary Sciences, 2018)
This study aimed to determine the densities of fiber follicles in the skin of the Karakaş, Norduz, and Zom sheep breeds and to carry out a comparative analysis between them. The study included a total of 36 animals aged 1-2 years and 3-4 years. Skin samples were obtained through biopsies taken from the right sides of the animals to determine the densities and ratios of the fleece follicles. Examination of these samples revealed that the primary follicle densities of the three sheep breeds (Karakaş, Norduz and Zom) were 3.11 ± 0.42, 3.14 ± 0.49 and 3.34 ± 0.59, while the secondary follicle densities were 8.42 ± 1.48, 8.51 ± 1.54 and 6.36 ± 1.44. The secondary to primary (S/P) follicle ratios of the sheep were 2.71 ± 0.70, 2.79 ± 0.69 and 1.85 ± 0.36, respectively. The primary follicle densities of the Karakaş, Norduz and Zom sheep were statistically similar for both age groups. The density of secondary follicles and S/P ratio decreased with age in both age groups. The similarity of the S/P ratios to those from other local sheep breeds suggest that Karakaş, Norduz, Zom sheep can be included in the sheep group that has coarse fleece.